Novel/magazine interfaces: the “long” serialisation of Wilkie Collins’s Armadale - Delafield, Catherine (Australasian Journal of Victorian Studies, 2020)
Wilkie Collins’s novel Armadale was published as a serial in Cornhill Magazine from November 1864 to June 1866. Delays in the writing and appearance of the serialised novel created unique interfaces between novel and magazine which are explored here. This article examines how the Cornhill’s first sensation novel Margaret Denzil’s History substituted for the absent Collins novel, and then traces Collins’s adaptation of his text to the Cornhill’s monthly format. The positioning of Armadale in the magazine suggests that Wives and Daughters took its place to disguise the sensational content. Trollope’s succeeding serial The Claverings was also intertwined within the magazine, and this article demonstrates how Armadale was effectively serialised over more than three years, not just in the twenty instalments appearing at the time. Readers at the time had an appreciation of the novels’ shared continuity and discontinuity that can be recovered by rereading these novels at their interfaces within the magazine. The paper explores the circumstances arising from the commissioning of Armadale to its conclusion and beyond to show how the periodical’s interface with the serial was prolonged.